2015
DOI: 10.1371/journal.pone.0118073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Associated SSR Markers for Yield Component and Fiber Quality Traits Based on Frame Map and Upland Cotton Collections

Abstract: Detecting QTLs (quantitative trait loci) that enhance cotton yield and fiber quality traits and accelerate breeding has been the focus of many cotton breeders. In the present study, 359 SSR (simple sequence repeat) markers were used for the association mapping of 241 Upland cotton collections. A total of 333 markers, representing 733 polymorphic loci, were detected. The average linkage disequilibrium (LD) decay distances were 8.58 cM (r2 > 0.1) and 5.76 cM (r2 > 0.2). 241 collections were arranged into two sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 50 publications
(77 reference statements)
8
58
5
Order By: Relevance
“…Similar observations were also made by Qin et al (2015). In the present study, except 3 associations (BNL-1440 with micronaire, BNL 3992 with micronaire and NAU-2363 with uniformity ratio), the remaining 29 associations of MLM were also detected by GLM.…”
Section: Resultssupporting
confidence: 91%
“…Similar observations were also made by Qin et al (2015). In the present study, except 3 associations (BNL-1440 with micronaire, BNL 3992 with micronaire and NAU-2363 with uniformity ratio), the remaining 29 associations of MLM were also detected by GLM.…”
Section: Resultssupporting
confidence: 91%
“…Additionally, qFS-c7 was also verified in F 2 and RIL populations [46]. qFS-c13-1 and qFS-c13-2 were detected in an RIL population [44] and a natural population [47], respectively. The stable QTL qFE-c22 was also confirmed as qELO-c22 in the previous study [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies showed a variable allele number per locus. For example, 2.13, 2.20, 5.46, and 7.64 alleles per marker have been found in several genetic diversity assessments for the cotton germplasm [26,59,60,61]. The semi-wild accessions retaining a diverse germplasm showed high allele numbers in the majority of studies consistent with a recent study because these accessions have not yet been exposed to extensive human selection pressure for accumulating a particular type of alleles [26,62,63].…”
Section: Discussionmentioning
confidence: 99%